Influence of Synthesizing Temperatures on the Crystallinity, Morphology and Band Gap of CdSe Thin Films - Vanderhyde, Cephas A.; Raut, Hemangi A. (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2022)
CdSe thin films were deposited using Chemical Bath Deposition (CBD) by maintaining the bath at 20 °C, 40 °C, 60 °C and 80 °C temperatures. The thin films were deposited on ordinary glass substrates then characterized for their crystallinity, morphological and optical properties. From the X-ray Diffraction (XRD) analysis; it was revealed that there was a significant difference in crystallinity and the UV-vis spectroscopy enhanced the study of the energy band gaps which showed a drastic shifting. The study performed on the surface morphologies of the CdSe thin films exhibited a double layer of deposition; but did not show considerable difference from each other for different temperatures. The EDS pattern helped in determining the stoichiometric ratio.